Determination of c-axis electrodynamics parameters of mercury cuprates - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2006)
The aim of this work is to introduce a number of electrodynamical parameters of mercury based CuO2 layered superconductors those relating electromagnetic or Josephson coupling. We have both calculated and compared superconducting condensation energy and coupling energy along the c-axis of mercury cuprates. Condensation energy and Josephson coupling energy have been calculated from the concept of thermodynamical critical magnetic field and Lawrence-Doniach Model [1], respectively. We have determined that these energies have the same value at low temperature. The other electrodynamical parameters such as Josephson penetration depth, plasma frequency, and anisotropy factor have also been found in the temperature range of 4.2-77 K. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: superconductivity; transport properties; oxides; critical phenomena; PLASMA RESONANCE; SUPERCONDUCTIVITY